P04.10 IDH-wildtype low grade gliomas: overall survival and prognostic indicators. (6th September 2019) - Berzero, G; Di Stefano, A; Ronchi, S; Villa, C; Marie, Y; Hoang-Xuan, K; Delattre, J; Mokhtari, K; Sanson, M
Abstract: BACKGROUND: IDH-wildtype WHO grade II diffuse gliomas represent a rare subgroup of low grade tumors characterized by poor prognosis. The clinical and molecular profile associated with these tumors has not been fully elucidated yet, and the ongoing uncertainties regarding their biological behavior hamper to establish a standard of treatment. The aim of this study is to define the median overall survival and the main prognostic factors associated with this rare tumor entity. MATERIALS AND METHODS: We performed a retrospective research in our center for all patients diagnosed with diffuse WHO grade II and III gliomas from 1976 to 2018. WHO grade II and III gliomas were divided into three molecular subgroups according to the IDH1/2 mutation and the 1p/19q codeletion status (1: IDH-mutant, 1p/19q codeleted; 2: IDH-mutant, 1p/19q non codeleted; 3: IDH-wildtype). We analyzed the clinical and molecular characteristics of the three subgroups, and then the clinical, radiological, histological and molecular features of IDH-wildtype WHO grade II gliomas. RESULTS: We identified 445 patients with diffuse WHO grade II gliomas, including 59 IDH1/2-wildtype tumors. IDH-wildtype grade II gliomas affected more frequently male (75% vs. 55%, p = 0.004) and older (mean age: 50.0 vs. 39.6 years, p<0.0001) patients, had frequent fronto-temporo-insular location (41%) and commonly underwent biopsy (53%) rather than resection. We found TERT promoter mutations (18/42, 43%), chromosome 7q gains (12/30, 40%), chromosome 10q losses (12/44, 27%), chromosome 9p losses (7/47, 15%), EGFR amplifications (5/51, 10%) and p16 deletions (4/50, 8%) but no P53 (0/16) mutations. Median overall survival was 46 months (vs. 98 for IDH-mutant non codeleted and 175 for IDH-mutant codeleted WHO grade II gliomas (p<0.0001); vs. 20 months for IDH-wildtype WHO grade III gliomas (p = 0.001)). Survival was not significantly influenced by age, preoperative KPS, tumor location, extent of resection or adjuvant treatment schemes. Chromosome 9p loss had a strong negative impact on overall survival (p=0.002). CONCLUSION: The median overall survival associated with IDH-wildtype WHO grade II gliomas does not exceed 4 years from diagnosis. As some genetic alterations seem to have a strong prognostic impact, an exhaustive genetic assessment can be helpful in this rare tumor group for purposes of prognostic stratification and treatment decision.